A Case Study on Experiential Learning in Architecture: Accessible, Climate-Responsive, and Flexible House Designs - Ali Berkay Avci; Şefika Gülin Beyhan (EMARA: Indonesian Journal of Architecture, 2022)
: Architectural education is based on acquiring theoretical and applied knowledge.  As a result, experiential learning theory was frequently applied to architecture design courses.  As experiential learning refers to gaining knowledge by doing, it allows the students to experience implementing the theoretical knowledge and refine their design solutions by communicating with the teachers.  The present study aims to integrate experimental learning in a theoretical course named "Building Information" on housing designs for first-year undergraduate architecture students.  After eight weeks of the theoretical lecture period, the students were assigned to design a house using one of the specific approaches, namely accessibility, climate responsiveness, or flexibility.  The occupants of the houses were defined, and the students determined their spatial needs.  After the critique sessions, the house designs were presented with drawings and analogue models as the final product.  Three selected examples from each design approach were evaluated in the study.  The results showed that the students gained and implemented theoretical knowledge more efficiently with the integration of experimental learning.